Assessment of the Biorisk Status of Veterinary Laboratories in Southwest Nigeria: Application of the Food and Agriculture Organization Laboratory Mapping Tool-Safety Module. (December 2020) - Adebowale, Oluwawemimo; Oduguwa, Adebankemo; Dipeolu, Saheed; Agbaje, Michael; Fasanmi, Olubumni; Fasina, Folorunso Oludayo
Introduction: Because of the nature of work conducted in veterinary laboratories and potential exposures to pathogenic microorganisms, good laboratory practices, risk assessments, biosafety, and biosecurity capacity is becoming vital. In this study, the Food and Agriculture Organization Laboratory Mapping Tool-Safety Module was applied to demonstrate its practical implementation in the assessment of biosafety and biosecurity statuses of veterinary laboratories in Nigeria. Methods: The Laboratory Mapping Tool-Safety Module, a standardized questionnaire, systematically and semiquantitatively gathered data on 98 subcategories covering 4 areas of biosafety and biosecurity capabilities: administrative, operational, engineering, and personal protective equipment. Results: Overall, the various areas and categories covered by the Laboratory Mapping Tool-Safety Module were weak across the board, with a mean performance of 19.5% (95% confidence interval, 14.0%-25.1%; range, 0.8%-29.6%). The weakest functionality was in emergency preparedness (0.8%; ie, emergency responses and exercises such as fire drills, spill cleanup, and biological spill kit availability). Also, many laboratories were deficient in metrology procedures, biosafety cabinets, chemical hazard containment, regular maintenance and external calibration procedures for laboratory equipment, and personnel health and safety. However, a few functionalities within individual laboratories scored above average (50%), for example, a university microbiology laboratory animal facility (100%). Interlaboratory comparison indicated that biosafety and biosecurity performance was similar across laboratories ( P = .07) and did not vary by location ( P = .37). Conclusions: Significant biosafety and biosecurity improvements are needed to guarantee the health and safety of workers and the global community, efficient responses to infectious disease containment, and compliance with the Global Health Security Agenda.